Does Financial Development Matter for Environmental Kuznets Curve in Russia? Evidence from the Autoregressive Distributed Lag Bounds Test Approach - Bass, Alexander; Burakov, Dmitry; Freidin, Max (International Journal of Energy Economics and Policy, 2019)
This study explores the relationship between carbon dioxide emissions and their main determinants, which include real income and energy consumption in Russia, employing data for the period 1990-2016. The hypothesis of financial development being an important determinant of environmental quality in Russia is also tested. For estimating the short-run and long-run relationships the ARDL bounds test approach is employed in this study. The results are consistent with the Environmental Kuznets Curve (EKC) hypothesis and show that the real income and energy consumption have a statistically significant positive impact on the carbon emission and its square has a significant negative effect on the carbon emissions both in the short-run and long-run. Financial sector is found to be significant determinant of carbon emission in Russia as well. The pairwise Granger causality test also reveals unidirectional causality running from financial development to the carbon emissions. Keywords: financial development, environmental Kuznets Curve, pollution, ARDL bounds test, carbon emission JEL Classifications: 016, 044, Q43 DOI: https://doi.org/10.32479/ijeep.7505